2013
DOI: 10.1371/journal.pone.0070614
|View full text |Cite
|
Sign up to set email alerts
|

A Unique Mitochondrial Transcription Factor B Protein in Dictyostelium discoideum

Abstract: Unlike their bacteriophage homologs, mitochondrial RNA polymerases require the assistance of transcription factors in order to transcribe mitochondrial DNA efficiently. The transcription factor A family has been shown to be important for transcription of the human mitochondrial DNA, with some of its regulatory activity located in its extended C-terminal tail. The mitochondrial transcription factor B family often has functions not only in transcription, but also in mitochondrial rRNA modification, a hallmark of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
10
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(11 citation statements)
references
References 59 publications
1
10
0
Order By: Relevance
“…produced undetectable amounts of transcripts, coexpression with Tfb1m improved transcription efficiency dramatically, to the point where it was suggested that Tfb1m may be the sole transcription factor necessary for mitochondrial transcription in D. discoideum (Manna et al, 2013). As illustrated above, mitochondrial function is dependent on nuclear-encoded protein import and this is facilitated by the TOM/TIM complexes in mitochondria.…”
Section: Dictyostelium Discoideum Homo Sapiensmentioning
confidence: 95%
See 1 more Smart Citation
“…produced undetectable amounts of transcripts, coexpression with Tfb1m improved transcription efficiency dramatically, to the point where it was suggested that Tfb1m may be the sole transcription factor necessary for mitochondrial transcription in D. discoideum (Manna et al, 2013). As illustrated above, mitochondrial function is dependent on nuclear-encoded protein import and this is facilitated by the TOM/TIM complexes in mitochondria.…”
Section: Dictyostelium Discoideum Homo Sapiensmentioning
confidence: 95%
“…While being shown to initiate transcription, RpmA, did so inefficiently, suggesting that, like other eukaryotes D. discoideum requires mitochondrial transcription factors for mtDNA transcription. Manna et al, (2013) identified and characterised a D. discoideum mitochondrial transcription factor B. Identified as tfb1m, this gene is 1,458 bp in size, with a corresponding amino acid sequence 485 residues in length, and approximately 56 kDa in molecular weight.…”
Section: Mitochondrial Transcriptionmentioning
confidence: 99%
“…This evolutionary relationship is supported by complementation studies. E. coli ksgA mutants lack methylated rRNA and are resistant to the aminoglycoside antibiotic kasugamycin [3,4]. The introduction of a mtTFB homolog into these mutants restores methylation and sensitivity to kasugamycin [4].…”
mentioning
confidence: 99%
“…E. coli ksgA mutants lack methylated rRNA and are resistant to the aminoglycoside antibiotic kasugamycin [3,4]. The introduction of a mtTFB homolog into these mutants restores methylation and sensitivity to kasugamycin [4]. Furthermore, the methyltransferase activity of mtTFB has been implicated in aminoglycoside-induced deafness, a disease involving hypermethylation of mutated mitochondrial small subunit rRNA and increased aminoglycoside sensitivity [3].…”
mentioning
confidence: 99%
See 1 more Smart Citation